The LC-MS/MS characterization of phenolic compounds in leaves allows classifying olive cultivars grown in South Tunisia. (June 2018) - Ben Mohamed, Mbarka; Guasmi, Ferdaous; Ben Ali, Sihem; Radhouani, Fedia; Faghim, Jihed; Triki, Tebra; Kammoun, Naziha Grati; Baffi, Claudio; Lucini, Luigi; Benincasa, Cinzia
Abstract: Olive ( Olea europaea L.) is one of the most important fruit species in the Mediterranean basin, where 95% of the world's olive orchards are planted, and has become an economically valuable crop worldwide due to an increasing demand in olive oil for human consumption. The aim of the present research was to classify Tunisian olive cultivars based on their phenolic profile and to test the potentiality of chemometrics as a tool for cultivars discrimination. The phenolic compounds present in 21 samples of olive leaves, collected during the normal picking period for olive oil production in South Tunisia, were analysed by liquid chromatography mass spectrometry. Models based on principal component analysis (PCA) and hierarchical cluster analysis (HCA) was used for discrimination purposes as a function of the tree varieties and cultivation zone. Qualitative and quantitative compositional analysis revealed 12 major phenolic compounds among which oleuropein (110.38–4741.62 mg/kg), hydroxytyrosol (5.40–290.19 mg/kg), apigenin 7- O -glucoside (9.44–2475.53 mg/kg), tyrosol (2.10–174.62 mg/kg), catechin (0–37.60 mg/kg) and vanillic acid (3.23–256.57 mg/kg) were identified. Oleuropein showed the highest amount in Fougi cultivar (4741.62 mg/kg), whereas the lowest level was registered in Zarrazi injassi cultivar (110.38 mg/kg). However, Zalmati Zarzis exhibited high concentrations of tyrosol, vanillic and caffeic acid, and vanillin. In general, rutin and luteolin 7- O -glucoside were the two main flavonoids detected. Dendrogram analysis revealed three main clusters, further confirmed through PCA. Graphical abstract: Highlights: Phenolic profile was investigated in leaves of South Tunisian olive cultivars. Twelve major phenolics were identified, with oleuropein being the most abundant one. Significant differences across cultivars could be outlined, regarding flavonoids and tyrosols Cluster analysis revealed three main clusters, further confirmed through PCA.